1998
DOI: 10.1088/0305-4470/31/11/017
|View full text |Cite
|
Sign up to set email alerts
|

Statistical mechanics of elastica on a plane: origin of the MKdV hierarchy

Abstract: In this article, I have investigated statistical mechanics of a non-stretched elastica in two dimensional space using path integral method. In the calculation, the MKdV hierarchy naturally appeared as the equations including the temperature fluctuation.I have classified the moduli of the closed elastica in heat bath and summed the Boltzmann weight with the thermalfluctuation over the moduli. Due to the bilinearity of the energy functional,I have obtained its exact partition function.By investigation of the sys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
41
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(41 citation statements)
references
References 53 publications
0
41
0
Order By: Relevance
“…While the Willmore surface is related to the modified Novikov-Veselov (MNV) equation, the elastica is related to the modified KdV equation [1][2][3][4][5][6][7][25][26][27]. Recently I exactly quantized the elastica of the Bernoulli-Euler functional (1-4) preserving its local length [25]. Then I found that its moduli is completely represented by the MKdV equation and closely related to the two-dimensional quantum gravity [28][29][30].…”
Section: §1 Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…While the Willmore surface is related to the modified Novikov-Veselov (MNV) equation, the elastica is related to the modified KdV equation [1][2][3][4][5][6][7][25][26][27]. Recently I exactly quantized the elastica of the Bernoulli-Euler functional (1-4) preserving its local length [25]. Then I found that its moduli is completely represented by the MKdV equation and closely related to the two-dimensional quantum gravity [28][29][30].…”
Section: §1 Introductionmentioning
confidence: 99%
“…Then I found that its moduli is completely represented by the MKdV equation and closely related to the two-dimensional quantum gravity [28][29][30]. The quantized elastica obeys the MKdV equation and at a critical point, the Painlevé equation of the first kind appears [25] while in the quantized two-dimensional gravity which is defined at a critical point of the discrete tiling model, there appears the Painlevé equation of the first kind with the KdV hierarchy [28][29][30].…”
Section: §1 Introductionmentioning
confidence: 99%
See 3 more Smart Citations